Analisis Kualitas Pelayanan Publik Di Badan Pelayanan Perijinan Terpadu Kabupaten Badung - Puspitasari, Ni Luh Putu; Bendesa, I K G (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.01.TAHUN 2016, 2016)
Good public service become a strategic policy issue because the public service has very broad implications especially in improving confidence in the government. The purpose of this study was to determine whether the variable physical evidence, responsiveness, reliability,  assurance and empathy as a determining factor in the quality of public services in license the Integrated Licensing Service Agency Badung regency, and to determine the influence of the quality of public services to regional revenue in Badung regency. This study population is people who have gained in the field of business licensing services to Small Enterprises in the Integrated Licensing Service Agency Badung regency , total sample of 100 respondents, of uptake in Proportionate Stratified Random Sampling, of the small number of micro enterprises by 60 and the number of medium enterprises as many as 607 businesses. The type of data collected and collected primary data by distributing questionnaires. The analysis technique used descriptive analysis and factor analysis. The results showed that: the five factors, factors of physical evidence, responsiveness, reliability, assurance, and empathy which consists of fifteen variables : The arrangement of the room, look officers, Infrastructure, Willingness officer, Smooth communication, administration of solutions, Certainty schedules, Clarity inforrmasi , speed processes, hospitality officer, clerk Ability, Responsibility, Caring officer, Justice and Security and comfort of the treatment. Variable officer responsibilities are variables that most affect the quality of public services in obtaining a business license in the Agency Licensing Services Integrated Badung regency because has the value of the highest coefficients , this means that a responsible attitude on the duties and functions of service providers that can be trusted by the community in helping the community seeker permits , especially for, Small Enterprises  in shaping the quality of public services in both so that more many existing businesses that directly affect the welfare of the community itself , and consciousness to legalize their business by completing licensing requirements , which means the higher the awareness of the public to pay taxes . Of the tax revenue it will directly affect the original revenue Badung regency.
Keywords: quality of public services